1999
DOI: 10.1177/016555159902500506
|View full text |Cite
|
Sign up to set email alerts
|

Korean international co-authorship in science 1994-1996

Abstract: Research performance in Korea has increased considerably in the past few years, both with regard to relative output of publications and the number of internationally co-authored papers. The purpose of this study is to characterise international scientific cooperation in Korea through the numbers of internationally co-authored papers covered by the Science Citation Index CD-ROM, 1994-1996. A total of 3,627 collaborative papers published in 1,083 scientific journals were selected to analyse papers written in col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…Recent studies [1][2][3][4] devoted to Korean scientific development, as measured by the number of research papers and their citedness in mainstream science journals, show an increasing presence of Korean authors in the world's scientific literature. Due to the efforts of the Korean Ministry of Education (MOE) and the Ministry of Science and Technology (MOST) to promote science and technology, there has been significant growth both in R&D expenditure and in the number of scientists and engineers in Korea.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies [1][2][3][4] devoted to Korean scientific development, as measured by the number of research papers and their citedness in mainstream science journals, show an increasing presence of Korean authors in the world's scientific literature. Due to the efforts of the Korean Ministry of Education (MOE) and the Ministry of Science and Technology (MOST) to promote science and technology, there has been significant growth both in R&D expenditure and in the number of scientists and engineers in Korea.…”
Section: Introductionmentioning
confidence: 99%
“…These findings support an earlier study conducted 14 which posited that international research collaborations are measured based on international co-authorship. International collaborations in research are essential for some types of research as they may be necessary for funding purposes and to increase research productivity 16 .…”
Section: Trends Of Collaborations Of Nigerian Medical Researchers Witmentioning
confidence: 99%
“…The rise of research cooperation between United States and Asia is another evidence of international knowledge transfer Katz & Martin, 1997;Kim, 1999). Due to data limitations, most studies focus on partnership/cooperation in publications (authorship), especially in scientific papers.…”
Section: Research Context: Business and Knowledge Linkagesmentioning
confidence: 99%
“…From a broad regional perspective, US co-authorship with Asia is on the rise compared to links with Western Europe (National Science Foundation, 2002). Without a doubt, this pattern reflects the ties of Asian students who received advanced training in the United States, an indicator of scientific cooperation between nations with a strong emphasis on science policy (Arunachalam & Garg, 1985;Basu & Kumar, 2000;Kim, 1999 Wagner et al (2001) interviewed scientists from developing countries and found that the advancement in information and communication technologies has been highly influential, although not decisive, in encouraging international collaborations. The majority of scientists reported that they began their collaborations either at a research site or at an international conference.…”
Section: Research Context: Business and Knowledge Linkagesmentioning
confidence: 99%